Metabolic engineering of Saccharomyces cerevisiae for 7-dehydrocholesterol overproduction - Xiao-Jing Guo; Wen-Hai Xiao; Ying Wang; Ming-Dong Yao; Bo-Xuan Zeng; Hong Liu; Guang-Rong Zhao; Ying-Jin Yuan (Biotechnology for Biofuels, 2018)
Abstract Background 7-Dehydrocholesterol (7-DHC) has attracted increasing attentions due to its great medical value and the enlarging market demand of its ultraviolet-catalyzed product vitamin D3. Microbial production of 7-DHC from simple carbon has been recognized as an attractive complement to the traditional sources. Even though our previous work realized 7-DHC biosynthesis in Saccharomyces cerevisiae, the current productivity of 7-DHC is still too low to satisfy the demand of following industrialization. As increasing the compatibility between heterologous pathway and host cell is crucial to realize microbial overproduction of natural products with complex structure and relative long pathway, in this study, combined efforts in tuning the heterologous Δ24-dehydrocholesterol reductase (DHCR24) and manipulating host cell were applied to promote 7-DHC accumulation. Results In order to decouple 7-DHC production with cell growth, inducible GAL promoters was employed to control 7-DHC synthesis. Meanwhile, the precursor pool was increased via overexpressing all the mevalonate (MVA) pathway genes (ERG10, ERG13, tHMG1, ERG12, ERG8, ERG19, IDI1, ERG20). Through screening DHCR24s from eleven tested sources, it was found that DHCR24 from Gallus gallus (Gg_DHCR24) achieved the highest 7-DHC production. Then 7-DHC accumulation was increased by 27.5% through stepwise fine-tuning the transcription level of Gg_DHCR24 in terms of altering its induction strategy, integration position, and the used promoter. By blocking the competitive path (ΔERG6) and supplementing another copy of Gg_DHCR24 in locus ERG6, 7-DHC accumulation was further enhanced by 1.07-fold. Afterward, 7-DHC production was improved by 48.3% (to 250.8 mg/L) by means of deleting NEM1 that was involved in lipids metabolism. Eventually, 7-DHC production reached to 1.07 g/L in 5-L bioreactor, which is the highest reported microbial titer as yet known. Conclusions Combined engineering of the pathway and the host cell was adopted in this study to boost 7-DHC output in the yeast. 7-DHC titer was stepwise improved by 26.9-fold compared with the starting strain. This work not only opens large opportunities to realize downstream de novo synthesis of other steroids, but also highlights the importance of the combinatorial engineering of heterologous pathway and host to obtain microbial overproduction of many other natural products.